2017
DOI: 10.1186/s13063-017-2031-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of daily all-over-body application of emollient during the first year of life for preventing atopic eczema in high-risk children (The BEEP trial): protocol for a randomised controlled trial

Abstract: BackgroundAtopic eczema (AE) is a common skin problem that impairs quality of life and is associated with the development of other atopic diseases including asthma, food allergy and allergic rhinitis. AE treatment is a significant cost burden for health care providers. The purpose of the trial is to investigate whether daily application of emollients for the first year of life can prevent AE developing in high-risk infants (first-degree relative with asthma, AE or allergic rhinitis).MethodsThis is a protocol f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 37 publications
1
52
0
4
Order By: Relevance
“…Regular use of emollients is the mainstay of AD treatment and can potentially prevent flares. [27][28][29][30][31][32] Preliminary data from a cohort study has shown a potential primary prevention interest for emollients, 33 however the results from a larger cohort in two studies did not confirm this hypothesis (European Academy of Allergy and Clinical Immunology (EAACI) 2019 Congress: Session HT 2 (Boyle) and abstract TP0986 (Skjerven). Presented June 2 and 3, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Regular use of emollients is the mainstay of AD treatment and can potentially prevent flares. [27][28][29][30][31][32] Preliminary data from a cohort study has shown a potential primary prevention interest for emollients, 33 however the results from a larger cohort in two studies did not confirm this hypothesis (European Academy of Allergy and Clinical Immunology (EAACI) 2019 Congress: Session HT 2 (Boyle) and abstract TP0986 (Skjerven). Presented June 2 and 3, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The BEEP study is a pragmatic, parallel-group, multi-centre, assessor-blind, randomized-controlled trial, details of which have been described elsewhere. 7 In brief, the BEEP study randomized 1395 participants between November 2014 and November 2016, recruited from 16 study centres across England. Participants were born at ≥37-week gestation and had a first-degree relative with parent-reported eczema, asthma or allergic rhinitis diagnosis.…”
Section: Beep Study Designmentioning
confidence: 99%
“…The Barrier Enhancement for Eczema Prevention (BEEP) study is a pragmatic, multi‐centre, randomized‐controlled trial of daily emollient use for the first year of life for primary prevention of eczema, in infants with a family history of atopic disease (ISRCTN21528841). Evaluation of IgE‐mediated food allergy was added to the initial study protocol after recruitment had commenced, but before any 2‐year follow‐up visits were conducted, once separate funding was secured . It was anticipated that a significant number of participants might decline to attend for OFC in BEEP, as the food allergy testing was presented to parents at the 2‐year visit as an optional sub‐study in a pragmatic, low‐contact trial with eczema prevention as its initial focus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, and perhaps more feasibly, WGS of the newborn can provide the same information, albeit a little later. In case mutations in skin barrier genes (like FLG) are detected, early intervention schemes can be applied, such as use of emollients soon after birth (205). In best case, such a personalized preventive strategy may hinder development of AD and its comorbidities (the atopic march) altogether.…”
Section: Atopic Dermatitismentioning
confidence: 99%